Compósitos à base de quitosana e fibras de celulose como um potencial sistema para liberação controlada de fertilizantes - Contieri, Gabriela Aparecida (Universidade Federal de São Carlos, 2021)
Chemical fertilizers are essential to the agrochemical industry when added to the soil to provide the nutrients needed for plant growth. As a more sustainable alternative, innovative and intelligent products are being developed, controlled-release fertilizers. This product offers an extended-release of nutrients to the plant in small amounts. The introduction of these materials in agriculture makes it possible to alleviate water contamination in rivers, groundwater, and the environment. This work aimed to improve the efficiency of using chemical fertilizers with the development of a composite prepared from chitosan and sugarcane bagasse fibers. Biodegradable polymers such as chitosan and cellulosic fibers have been explored to develop “green” composite materials with properties of great technological interest, such as prolonged nutrient release capacity. Chitosan is insoluble in water, making its use as a coating matrix viable, acting as a hydrophobic barrier that will reduce the availability of nutrients to the environment. Cellulosic fibers, in turn, act as a biosorbent medium for nutrients, helping to delay their release. Additionally, the sorbed fibers were characterized by morphological techniques (Scanning Electron Microscopy (SEM), structural (Infrared Region Spectroscopy (FTIR), X-ray diffraction (DRX), and thermal (TGA) methods. It has the potential to be a controlled-release fertilizer due to its promising sorption results. Moreover, concerned with the current educational scenario, new didactic proposals are needed to ensure quality teaching; the Interdisciplinary Island of Rationality proposes a teaching emancipatory and makes the students the protagonist of their education. More current themes can be worked on, such as the insertion of biopolymers in organic chemistry teaching.
Composites based on chitosan and cellulose fibers as a potential system for controlled release of fertilizers
Keywords: Ferti liberadores; Compósitos; Polímeros; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA